Penegakan Hukum Terhadap Larangan Bisnis Pakaian Bekas Impor (Studi Kasus Di Dinas Perdagangan Kab. Lombok Timur): Law Enforcement Regarding Prohibiting The Imported Second-Hand Clothing Business (Thrifthing) (Case Study In The Trade Department East Lombok Regency) - army, putri (Fakultas Hukum Universitas Gunung Rinjani, 2023)
This research was motivated by the widespread discovery of sales of imported used clothing in East Lombok, especially in the Masbagik area. The focus of this research refers to the problem formulation, namely the provisions of the regulations prohibiting the imported second-hand clothing business according to the law and how the District Trade Department's efforts. East Lombok in enforcing the law against the imported second-hand clothing business which aims to minimize irregularities in imported second-hand goods. The research method used in this research is Normative-Empirical research. Data collection techniques use interview techniques and literature study. The approach methods used are the conceptual approach, case approach and statutory approach. So the results of this research show that the provisions of the rules prohibiting the imported second-hand clothing business are contained in the Minister of Trade Regulation of the Republic of Indonesia No. 51/M-DAG/PER/7/2015 concerning imported second-hand clothing being prohibited from being imported into Indonesian territory and efforts to enforce the law are being carried out. by the Trade Service is only limited to controlling locations and communicating with the provincial government to carry out control at the import level.